Innovation Management in the Finnish Construction Business. A Case Study of Development of Innovation Management Processes - Matinaro, Ville (My University, 2015)
In the Finnish construction business, innovation management is commonly regarded as difficult due to the industry’s characteristics. Some of the difficulties seem to be in the very nature of the construction industry itself, such as its cyclical nature and project-based way of working which are not ideal for innovation management. Organizational innovativeness needs good cooperation skills throughout the organization. In the case of a project-based industry it is essential that innovation processes happen in the projects themselves. Communication skills and channels between the company level and projects are essential for innovations. In comparison with other industries, it seems that generic innovation models do not apply to the construction industry because of its different nature. This study addresses and answers three research questions: (1) How can an effective organizational innovation management processes in construction industry be developed? (2) What kind of model will describe these processes well in the construction industry’s multileveled and inter-organizational environment? and (3) How can organizational innovativeness in the case company be increased? The main findings are that organizational culture, the ability of managers to lead people, and soft issues in the construction industry seem to be more relevant matters concerning innovativeness than actual process descriptions, even though structures are also needed. Incorporating innovativeness into the company’s systems and way of working could be the answer to increasing innovativeness in the case company. This thesis is a case study of a real company which operates in the Finnish construction industry.
Keywords: Innovation; management; organizational culture; organizational learning; communication; collaboration; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|